Penyelesaian Hukum Terhadap Sengketa Wanprestasi Dalam Perjanjian Kerja Yang Dilakukan Oleh Perusahaan Black On Box Cafe&Convention - Rakha Fadhillah; Arief Suryono (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the legal settlement undertaken by Black On Box Cafe & Convention and its workers, namely, Juniati Tamil related to the emergence of breach of contract which will be reviewed by the Civil Code and Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes. In this study, the type of legal research used is perscriptive normative legal research with secondary data types including primary and secondary legal materials. The technique of collecting legal materials is carried out with literature, then used The analysis technique used is the deductive method. This study produces the author's views on legal settlement against breach of contract which is reviewed by the Civil Code and Law No. 2 of 2004.